Metaphoric Expressions on Vertical Axis Revisited: An Empirical Study of Russian and French Materia - Luodonpää-Manni Milla; Viimaranta Johanna (Taylor and Francis, 2022)
The purpose of this article is to study the use of “UP–DOWN” metaphors in Russian and French material. A list of 10 conceptual metaphors expressing up–down movement was proposed by Lakoff and Johnson (1980), and this list has been reproduced many times since. However, this analysis shows that the list is not fully accurate. In addition to the conceptual metaphors proposed by Lakoff and Johnson, the authors find it important to include 5 more metaphorical models expressing vertical movement. On the other hand, 5 of the conceptual metaphors in Lakoff and Johnson’s list turned out not to be relevant to this analysis. The authors also attempt to describe the connections between different metaphoric models and observe that not all metaphoric models are equally important in their evidential and conceptual power.